World upside down: reading Acts in the Graeco-Roman world - Rowe, Christopher Kavin (Oxford University Press, 2009)
Reading Acts -- Collision : explicating divine identity -- Dikaios : rejecting statecraft -- World upside down : practicing theological knowledge -- The apocalypse of Acts and the life of truth